PRIMARY CHEILITIS: PATHOGENETIC APPROACHES TO TREATMENT - Marchenko, A.V. (World of Medicine and Biology, 2021)
Primary cheilitis is widespread among all lip diseases. The article presents known methods of treatment and maintenance therapy of cheilitis and offers its own methods of treatment and maintenance therapy of meteorological and actinic cheilitis in patients. Pathogenetic therapy has the main task of achieving long-term control over the symptoms of meteorological and actinic cheilitis, aimed at preventing exacerbations of the disease during the year. All patients in the observation group received comprehensive therapy and were recommended to undergo maintenance therapy 3, 6 and 9 months after the main course of cheilitis treatment. Treatment was considered effective in achieving positive results in the subjective and objective picture of the disease. The data obtained indicate that the drug tiotriazoline should be used in the medical treatment of patients with meteorological and actinic cheilitis. The necessity not only of local treatment, but also of its systemic application in complex therapy is proved. For the general therapy of actinic cheilitis for the purpose of hyposensitizing effect it is expedient to appoint antihistamines of the third generation.
Keywords: primary cheilitis; meteorological cheilitis; actinic cheilitis; treatment; maintenance therapy